Analysis of Policy Making Factors on The Prohibition of Hormones and Antibiotics Use for Feed as a Public Health Protection - Amalia, Zaima; Adisasmito, Wiku (UI Scholars Hub, 2017)
Food safety is one of the current international emerging issues. The danger of using antibiotics in animal husbandry is one of the contributors to human resistance. In Indonesia, antibiotics are commonly used as growth promoters in animal husbandry. Prohibition on the use of hormones and antibiotics mixed into animal feed written in Law No. 18 of 2009 on Animal Husbandry and Health which is then clarified by the Minister of Agriculture Regulation No. 14/Permentan/PK.350/5/2017 on the Classification of Animal Drugs. The purpose of this study is to determine the factors which influence the formation of policy on the prohibition of hormone and antibiotic use as feed additives, especially health, legal, political and economic factors. This research uses descriptive study by qualitative approach. Data were collected using in-depth interviews and literature studies. The result shows that legal factors have a stronger influence than health, economic and political factors. The study recommends that the government should develop monitoring programs, conduct surveillance in feed and breeder entrepreneurs, establish good coordination with local governments, conduct further residue studies on animal source food, and further review the economic impact of the policy. Breeders also need to improve the cleanliness of the cage and try natural feed. While feed entrepreneurs need to find a replacement of antibiotic/hormone mixed feed safely.